(3bQGAGJ aj fXQjI GdMJejI GdbjejI aj GdGYdGe (B/s - (3fUjQ, HhYdjs ((3GdLRGFQ (B:s (3OGQ GdCjGe ,s, 2009)
(3eKd fXQjI GdMJejI GdbjejI aj GdEYdGe(B-(3GdefJSHI Edi KdI ef GdHGMKjf aj GdYGde GdYQHj HbjGOI GdCSJGP GdOcJhQ YHO GdQMef YRj(B-(3eOQSI dgG eQLYjJgG GdYdejI GdJj LYdJgG aj MGdI bWYjI eYQajI eY GdeaGgje GdSGFOI MGdjG aj Mbd GdEYdGe h GdGJUGd(B. (3JNhV gPg GdOQGSI aj JMdjd h Jacjc GdfSb GdacQj h GdeYQaj GdPj HdhQ eaGgje gPg GdfXQjI h JHMK aj echfGJ gPG GdfSb GdeJeKdI aj GdJQGK GdYQHj h GdESdGej h GdacQ GdadSaj h GdGLJeGYj GdeYGUQ h CHSJehdhLjG GdGJUGd h GdEYdGe ef NdGd GdeaGgje GdLOjOI GdJGdjI (B: (3ebGQHI LOjOI deaghe GdKbGaI, GdYhdeI, GdeNjGd GdEYdGej, GdRef GdEYdGej, GdecGf GdEYdGej, GdNha GdEYdGej, GdQCS eGd GdEYdGej GdQeRj(B..... (3gPg GdeaGgje eQJHWI fSbjG HfXQjI GdMJejI GdbjejI aj GdEYdGe h JaSQ ef GdOGNd hGbY GdEYdGe GdYQHj h GdESdGejs
Keywords: (3GdGYdGe s; (3GdMJejIs